PERAN BALAI PEMASYARAKATAN (BAPAS) DALAM PROSES PENYELESAIAN TINDAK PIDANA YANG DILAKUKAN ANAK BERBASIS RESTORATIF JUSTICE - Margie Gladies Sopacua (SASI, 2015)
The perpetrators did not know the age, even children can also be perpetrators of crime, and punishable by imprisonment, so that his rights as a child threatened by the state, such as the right to education, and play, for the Hall of Correctional (BAPAS) kids there for protect the rights of children in conflict with the law to realize Restorative Justice. BAPAS role in the process of the juvenile justice system is necessary, to carry out diversion as a form of restorative justice. Protection of children rights should be at the stage before the trial, the trial and after the trial. Furthermore it is necessary to increase human resource officer BAPAS, judges, prosecutors and police for dealing with juvenile delinquents to achieve restorative